Geoquímica e distribuição dos metais traço em testemunhos de sedimento do açude Marcela, Itabaiana - Sergipe - Santos, Izaias Souza dos (2010)
This study addresses the distribution of trace metals in sediment cores from the dam Marcela in order to evaluate the occurrence of impacts associated with human and industrial activity. The dam is located in the city Itabaiana in the state of Sergipe, it was built in the period 1953 - 1957 barring Fuzil stream. It has an area of 1.4 km2 with storage capacity of 2,700,000 m3. Two sediment cores were collected in November of 2008 with approximately 45cm in two distinct points. The samples were sectioned in 5 cm each and they were analyzed by to determine the following chemical elements: Co, Cr, Cu, Ni, Pb, Zn, Mn, Al, Fe, Corg and Ntotal. The average value of Corg/Ntotal in the range 4,97- 7,64 and 6,39-7,69, for cores I and II respectively, indicative autochthonous and allochthonous origin of the organic matter. The multivariate statistical analysis (Principal component analysis) applied to the set of results showed that the two cores in relation to concentrations of metals are different, with evidence of enrichment for Cr, Cu, Mn and Zn in the surface layers. The contamination factor calculed showed contamination moderate level for metals Cr, Cu, Mn and Zn. The risk assessment code (RAC), which consider the percentage of metal extracted in the label fraction (F1) of BCR procedure, showed that chromium does not present risk to the environment, copper, nickel and lead were low to medium risk, and zinc had of very high to High risk to the aquatic environment. Small variations in environmental conditions, such as pH or salinity, could therefore increase availability of the elements to the aquatic system. The metals concentrations were always at the lower limit the TEC and PEC, defined by consensual sediment quality guidelines (SQGs), in this case, it is not possible to predict what adverse effects the metal can cause in this environment.